RETRACTED: Evaluasi Program Gala Desa Tahun 2017 di Kementerian Pemuda dan Olahraga - Rani Aggra Berta Yagusta; Widiastuti Widiastuti; Wahyuningtyas Puspitorini; Karisdha Pradityana (UIR Press, 2019)
This article has been withdrawn at the request of the Chief Editor. The reason for the withdrawal is because this article was also published in the Prosiding Seminar dan Lokakarya Fakultas Ilmu Keolahragaan Universitas Negeri Jakarta. (http://journal.unj.ac.id/unj/index.php/prosidingfik/article/view/10727). The condition for submitting a work for publication is that the author explicitly states that all of his works are original and have not appeared in publications elsewhere. We apologize to journal readers that this was not detected during the delivery process.